Goal! What happens before and after the goal? The demands of competition before and after a goal are different from the average match - Asian-Clemente, J. A.; Galiano, C.; Muriarte, D.; Beltrán-Garrido, J. V.; Asín-Izquierdo, I. (International Journal of Sports Science & Coaching, 2025)
The objectives were: 1) compare the external load before and after a goal with average match demands, and 2) analyze differences in response of players pre and post goal scored and conceded. 23 official matches of twenty-two youth professional soccer players (age = 20.6 ± 1.8 years, weight = 73.0 ± 7.1 kg, and height = 1.80 ± 7.4 m) were monitored. With Global Positioning System (GPS) were obtained the Distance Covered (DC), DC >21 km·h-1, DC >24 km·h-1, Player Load, accelerations and decelerations (±2-3 m·s-2 and ±3 m·s-2) during the mean of the matches (Team) and in the 5 and 10 min before (Pre5 and Pre10) and after (Post5 and Post10) the goals scored and conceded. DC >24 km·h-1 was higher to the Team in all periods independently of the goal status (p = 0.05). Similarly, Team showed lower DC >21 km·h-1 than Pre5 in goals scored and Post5 in goals conceded (p = 0.05). DC, Player Load (except, Pre10), as well as much of the accelerations and decelerations periods were reduced when the goal was conceded (p = 0.05). Similarly, accelerations and decelerations were reduced in Post5 when the goal was scored, including accelerations between 2-3 m·s-2 in Post10 and higher than 3 m·s-2 in Pre5 (p = 0.05). Comparing the same period of scoring or conceding a goal, small differences were observed with higher values during goals scored (p = 0.05). Around goal moments, players` external load change compared to the match average, varying depending on whether the goal is scored or conceded, and the period analyzed.